Implementation of the Stabilizing Function of a Fiscal Policy in the Eurozone Countries - Markowski, Łukasz (Olsztyn Economic Journal, 2022)
The implementation of a stabilizing fiscal policy is of particular importance to the eurozone countries, which do not have the ability to make autonomous decisions in the scope of their monetary policy in order to ease fluctuations of an economic cycle. The aim of this research was to evaluate the implementation of a discretionary fiscal policy in selected countries of this bloc. The ex post analysis of the approaches to national fiscal policies, with a division into two research sub-periods, was conducted with statistical methods. Based on the official forecasts by the European Commission, a “real time analysis” was also made, which to some extent enables gaining an insight into plans and intentions of the governments at the moment of making budgetary decisions. The results call into question the use of discretionary fiscal policies in stabilizing the economic cycle at the national level in the studied Eurozone countries. It can be said that the reforms implemented after the financial and economic crisis had a limited impact on the intentions and the actual implementation of the fiscal policies in an anti-cyclical manner. It is then sensible to consider alternative mechanisms, which could successfully lessen the asynchronous fluctuations in production within the European monetary union.